IMPLEMENTASI STRATEGI PEMASARAN DAN PEMBUKUAN PENJUALAN BAGI PELAKU UMKM DI KOTA PALEMBANG PROVINSI SUMATERA SELATAN - Agustini, Triana; Widarti, Widarti (Gapenas Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in driving regional economic growth, including in Palembang City. Community service carried out by the Faculty of Economics aims to foster interest and see direct practice regarding the implementation of marketing strategies and sales bookkeeping for MSME partners in Palembang City. Community service is carried out by conducting direct visits by the Faculty of Economics, Tamansiswa University of Palembang to MSMEs in Palembang City. The implementation method in this activity is a workshop providing training and counseling to MSME partners. The results of the workshop activities have been carried out well and are quite relevant. The workshop participants, namely MSME actors in Palembang City, were enthusiastic about participating in this activity. With the workshop activities, participants have knowledge, new insights, and understanding regarding the implementation of marketing strategies and sales bookkeeping that can be practiced for product marketing and sales.